Carvalho Poetry Selections (AmeriQuests, 2010)
The following poems are part of a larger cycle of work entitled _“If the radiance of a thousand suns”: Songs of the American Hiroshima_, which examine the complex familial and societal relationships that develop amid a backdrop of nuclear proliferation. The poems featured in the attached selection correspond with sections II and III of the manuscript, "Please Stand By," and "American Hiroshima," respecitively.